2020
DOI: 10.1016/j.annonc.2020.08.966
|View full text |Cite
|
Sign up to set email alerts
|

827P First real-life data on olaparib in 1st line (1stL) maintenance BRCA1/2 mutated epithelial ovarian cancer (EOC) in France: Descriptive analysis of 201 patients (pts) enrolled in the cohort temporary authorization for use (ATUc)

Abstract: as monotherapy for the maintenance treatment of adult patients with platinum-sensitive relapsed (PSR) BRCA-mutated OC who are in response to platinum-based chemotherapy (PBC). In addition, film-coated tablets were approved in the EU in May 2018 for PSR-OC regardless of BRCA status, and in June 2019 for adult patients with advanced BRCA-mutated OC who are in response to first-line PBC. So far, only limited data on real-world maintenance monotherapy with olaparib are available. We evaluated HRQoL during olaparib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The separate standalone safety and efficacy findings from the China cohort of SOLO2 (consisting of 32 randomized patients from sites in China) (25) showed similar results. (26). In this study, olaparib was well tolerated and no new safety signals were observed in this setting.…”
mentioning
confidence: 61%
“…The separate standalone safety and efficacy findings from the China cohort of SOLO2 (consisting of 32 randomized patients from sites in China) (25) showed similar results. (26). In this study, olaparib was well tolerated and no new safety signals were observed in this setting.…”
mentioning
confidence: 61%
“…From 11 March, 2019 to 16 January, 2020, 107 centres requested inclusion for 238 patients; 201 requests were accepted, 28 were denied because they did not meet the ATUc criteria and 9 requests were awaiting additional information on 16 January, 2020, and were ultimately deemed as not acceptable for inclusion in the ATUc. The main reason for the ATUc exclusion was that the time between the last chemotherapy cycle and the request was greater than 8 weeks (Table 1) [15]. A total of 194 patients received olaparib maintenance therapy.…”
Section: Patientsmentioning
confidence: 99%
“…National coverage is shown in Fig. 1 [15]. Five requests (3.0%) were made by physicians from the French Overseas Departments and Territories: Guadeloupe and Ile de la Réunion.…”
Section: Requestersmentioning
confidence: 99%
See 2 more Smart Citations